TRANSFORMASI DIGITAL DALAM MERANCANG OCEANARIUM STRATEGI JITU MENJADI WISATA UNGGULAN - Wiraguna, Sidi Ahyar Wiraguna; L.M.F Purwanto (UNIVERSITAS STEKOM, 2024)
Oceanarium s are popular tourist destinations in Indonesia. This article discusses digital transformation in designing the latest Oceanarium. The research method involves surveys and observations to 2 major Oceanarium locations in Jakarta, one Oceanarium in Singapore and one in Bangkok's Siam Paragon, to get an overview of operations, and the implementation of digital technology. In addition, this research also integrates the author's experience as a public aquarium designer and for 20 years as a manager in one of the public aquariums in the Jakarta area. The current approach needs to involve the integration of IoT technology for aquatic environment monitoring, smart energy management system. The results show that the implementation of interactive technology in several places can create an interesting and memorable learning experience for visitors. One of the technologies that is interesting and preferred by visitors is the use of hologram technology, visitors can feel the sensation of being in the sea and interact with marine animals in a realistic virtual environment. This enhances their understanding of marine flora and fauna and the importance of preserving the marine environment. This digital transformation not only improves the operational efficiency of the Oceanarium, but also enriches the visitor experience through the application of interactive technology. By implementing this strategy, Oceanarium s in Indonesia are expected to continue to grow, make a positive contribution to the preservation of the marine environment, increase public knowledge of marine biology, and provide a high-quality experience for visitors.